IMPROVING STUDENTS’ READING COMPREHENSION USING BIG BOOK - Fahmi, Dita Indah; Suhartono, Luwandi; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research is intended to know how well the use of Big Book in improving student’s reading comprehension of the fifth grade students of SDN 32 Pontianak. The purposes of this research is to help students to cope with their problem in reading comprehension using Big Book. Students are able to comprehend the reading text. This research was a classroom action research which was conducted on the purpose to solve the problem that happened in the classroom action and to improve the teaching learning process. The data of classroom action research were collected through achievement test, field note and observation checklist. This research implemented three cycles, namely: planning, acting, observing and reflecting. The use of Big Book in improving students reading comprehension can be seen in every meeting or cycles that was observed by the researcher and her collaborator. Keywords: Big Book, Classroom Action Research, Reading Comprehension. Abstrak: Penelitian ini untuk mengetahui manfaat penggunaan buku besar untuk meningkatkan kemampuan siswa kelas 5 SDN 32 Pontianak dalam pemahaman membaca. Tujuan dari penelitian ini membantu siswa untuk menyelesaikan masalah mereka dalam pemahaman membaca dengan menggunakan buku besar. Siswa- siswa diharapkan bias memahami isi dari bacaan teks. Penelitian ini adalah penelitian tindakan kelas yang bertujuan untuk mengatasi masalah yang terjadi di dalam kelas dan untuk meningkatkan kegiatan proses belajar mengajar. Data dari penelitian tindakan kelas ini dikumpulkan dari tes pencapaian, catatan-catatan lapangan dan pengamat checklist. Penelitian ini dilaksanakan dalam 3 siklus dan 4 langkah dalam setiap siklusnya: perencanaan, tindakan, observasi dan refleksi. Penggunaan buku besar untuk meningkatkan kemampuan siswa dalam pemahaman membaca bias dilihat dalam setiap pertemuan atau siklus yang sudah d amati oleh peneliti dan kolaborator. Kata kunci: Buku Besar, Penelitian Tindakan Kelas, Pemahaman Membaca.